Correlation of cancer types with stages and symptoms: analysis-based descriptive cross-sectional study - Uddin, Sharika Suhrat Bushra; Akther, Fahmeda; Shahriar, S.M Shakil (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.